Pengaruh Work Life Balance, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT PLN (PERSERO) UP3 BENGKULU - Edo Zulkarnain; Juhaini Alie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of work-life balance, work motivation, and job satisfaction on employee performance at PT PLN (Persero) UP3 Bengkulu. A quantitative research approach was employed using questionnaires as the data collection method. The population consisted of 126 employees, and a saturated sampling technique was applied. Data were analyzed using multiple linear regression after passing classical assumption tests. The results indicate that work-life balance, work motivation, and job satisfaction individually have a positive and significant effect on employee performance. Simultaneously, these three variables also significantly influence employee performance, with job satisfaction being the most dominant factor. The findings suggest that improving employee performance requires an integrated human resource management strategy that supports work-life balance, enhances motivation, and ensures job satisfaction.